How to Stabilize Video in Cap Cut so it doesn't shake 100% Successfully - rosari J (Caring : Jurnal Pengabdian Masyarakat, 2021)
Frequently, you will come with the results of exciting video footage. What am I supposed to do with that? We'll look at how to stabilize a rocking video on Android in this article. The majority of smartphones now have high-resolution cameras.How to Use Cricut to Stabilize Rocking Videos - Capcut is one of the most popular video editing apps on Android right now. With the Capcut application, we can simply edit our videos on Android without the use of a PC or computer. Furthermore, the capabilities provided by this capcut application are many and unquestionably simple to use.We can trim videos, add music to them, apply effects and transitions, turn images into anime and comics, stabilize films, and much more with Capcut. The video stabilization option is one of the features I'll describe right now. This feature allows you to stabilize the rocking video, which is useful because our video sometimes shakes when we take a picture while walking or on the road. Using this strategy, your movie will undoubtedly feel smoother and smoother, with no wobbling.Our altered videos will be able to export / save without watermarks thanks to this capcut tool. When we export most video editing apps from the Play Store, we get watermarks, however with this capcut software, we can remove the watermark at the end of our movie timeline and save our videos without the watermark.